A pro-oxidant combination of resveratrol and copper down-regulates hallmarks of cancer and immune checkpoints in patients with advanced oral cancer: Results of an exploratory study (RESCU 004) - Pilankar, Aishwarya; Singhavi, Hitesh; Raghuram, Gorantla V.; Siddiqui, Sophiya; Khare, Naveen Kumar; Jadhav, Vishalkumar; Tandel, Harshali; Pal, Kavita; Bhattacharjee, Atanu; Chaturvedi, Pankaj; Mittra, Indraneel (Frontiers in Oncology, 2022)
Background: Our earlier studies have shown that cell-free chromatin particles (cfChPs) that are released from dying cancer cells are readily internalised by bystander cells leading to activation of two hallmarks of cancer viz. genome instability and inflammation. These hallmarks could be down-regulated by deactivating cfChPs via medium of oxygen radicals generated upon admixing small quantities of the nutraceuticals resveratrol (R) and copper (Cu). In this exploratory study, we investigated whether oral administration of R and Cu (R-Cu) would down-regulate the hallmarks of cancer and immune checkpoints in advanced squamous cell carcinoma of oral cavity (OSCC). Patients and methods: The study comprised of 25 patients divided into 5 equal groups. Five patients acted as controls; the remaining 20 were given R-Cu in four escalating doses. The lowest dose of R-Cu was 5.6mg and 560ng respectively, and the highest dose was 500mg and 5mg respectively. An initial biopsy was taken from patients at first presentation, and a second biopsy was taken 2 weeks later on the operating table. R-Cu was administered orally twice daily in the intervening period. Confocal microscopy was performed on tumour sections after fluorescent immuno-staining with anti-DNA and anti-histone antibodies to detect presence of cfChPs in the tumour micro-environment (TME). Immunofluorescence analysis was performed for 23 biomarkers representing the 10 Hallmarks of cancer, including 5 immune checkpoints, defined by Hanahan and Weinberg. Results: Confocal microscopy detected copious presence of cfChPs in TME of OSCC, which were eradicated / deactivated following two-week treatment with R-Cu. Eradication of cfChPs from TME was associated with marked down-regulation of 21 / 23 biomarkers, including the five immune checkpoints. The lower two doses of R-Cu were more effective than the higher doses. No adverse effects attributable to R-Cu were observed. Conclusion: These results suggest that cfChPs released into TME from dying cancer cells are global instigators for cancer hallmarks and immune checkpoints in surviving cancer cells. The ability of R-Cu to deactivate cfChPs raises the prospect of a novel and non-toxic form of cancer treatment which sans killing of cancer cells, and instead induces healing by down-regulating cancer hallmarks and immune check-points.